A Review of Common Research Methodologies Used in Social Sciences - Neelam Singh, (AG Volumes, 2025)
This review will consider the research methodologies that are widely applied in the social sciences with a focus on their philosophical underpinnings, their use, their advantages, and their drawbacks. It addresses the issues of quantitative, qualitative, and mixed-methods research, and shows the role of each methodology in gaining the insight into the complex social phenomena. The review provides the description of the main data collection methods, such as the surveys, interviews, observations, and secondary data analysis, as well as the main ethical aspects of the research, such as informed consent, confidentiality, and safeguarding the vulnerable population. The latest developments in the form of big data analytics, artificial intelligence, digital ethnography, and open science practices are also discussed highlighting the necessity of growing flexibility of methods, rigor, and integration in modern social science studies.